ANALISIS HUKUM ISLAM TERHADAP TEKS TAKLIK TALAK DALAM BUKU NIKAH MENURUT MADZHAB AS-SYAFI’I - Rahman, Arif (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2023)
This research aims to examine further the text of taklik talak as a form of marriage agreement in the marriage book according to the Imam Syafi'i school of thought. Using literature research in reviewing it, the law of divorce in marriage is permissible and depends on the agreement of the husband and wife. Although not mandatory, this agreement is usually included in the marriage certificate book. After the marriage contract, PPN offers the husband to read and sign the divorce agreement. If the husband agrees and signs, the agreement is considered valid, even if it is not read during the marriage contract. Even though the law is permissible, the contents of the agreement have been determined by the Ministry of Religion, making it a standard agreement. The determination of the divorce agreement in the marriage certificate reflects custom, although it is not legally required. The validity of the taklik talak agreement cannot be revoked once it is deemed valid.